The creation of debility and disability in South Africa: Colonial and apartheid encounters - Lieketseng Y. Ned (South African Journal of Science)
The global legacy of colonialism has historically been studied in disciplines ranging from sociology and human geography to development economics, political sciences and international relations. However, over the years, the field of public health has also seen an emergence of research on the impacts of colonialism on the health outcomes of populations in the Global South. Operating at the nexus of the field of disability studies and decoloniality, I critically historicise South Africa’s colonial and apartheid encounters, with specific reference to how they created debility and disability. I argue that, while disability existed in pre-colonial African societies, including in South Africa, it was not deemed as an impairment that eroded the humanity and value of persons with disabilities. The construction of disability as an impairment, and the consequences related to this construction, emerged out of colonial and apartheid encounters. Both epistemologically and through layered forms of violence, colonialism and apartheid created debility and disability. Situating discourse in the field of disability studies within the context of colonial and apartheid encounters in the Global South in general, and South Africa in particular, is crucial. It is especially necessary that such discourse be anchored in decolonial theorisation in order that the particularities of the experience of disability in post-colonial and post-apartheid societies can be understood within this context.